If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 13(19 + -1x) = 211 11x + (19 * 13 + -1x * 13) = 211 11x + (247 + -13x) = 211 Reorder the terms: 247 + 11x + -13x = 211 Combine like terms: 11x + -13x = -2x 247 + -2x = 211 Solving 247 + -2x = 211 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-247' to each side of the equation. 247 + -247 + -2x = 211 + -247 Combine like terms: 247 + -247 = 0 0 + -2x = 211 + -247 -2x = 211 + -247 Combine like terms: 211 + -247 = -36 -2x = -36 Divide each side by '-2'. x = 18 Simplifying x = 18
| -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 | | 52=(3x+2) | | 3(x+3)+x=2(x+3)-5 | | 9x^2+27x=7 | | y=3x^2-7x-1 | | 0.2(x-2)-0.4(x+2)=-0.2x-0.4 | | (R-2)3+6=38.85 | | 3t+16.9=(11+-29.5) | | 11-2x=2(4-x) | | 10z=6z-10+3z | | (-3x^2y^4)(8xy^3)=0 | | 9x+48=2x+11 | | 20(-3+2x)=(4x)5 | | 10ac-x=3 | | 8(x+6)+x=2(x+2)+7 | | -8(-2x+5)=-136 | | 2(-10-7x)=50 | | 2(5-1.7b)=15.1-7(1.7) | | 2v-3v+3-4v=0 | | (3x-5)(x-8)=0 | | 11+6y-8y=-3+3y | | 13x-4=7x-22 | | 48-32=4(12-x) | | -2gh(g^3h^5)=0 | | 7x+2=4x-9 | | 8b-8=-6(b-3)+6(1+2b) | | 12x-14=16x | | -(1+7x)-6(-7-x)=6 | | 7n-8+2+7n=0 |